Content is King: An Analysis of How the Twitter Discourse Surrounding Open Education Unfolded From 2009 to 2016 - Paskevicius, Michael; Veletsianos, George; Kimmons, Royce (International Review of Research in Open and Distributed Learning, 2018)
Inspired by open educational resources, open pedagogy, and open source software, the openness movement in education has different meanings for different people. In this study, we use Twitter data to examine the discourses surrounding openness as well as the people who participate in discourse around openness. By targeting hashtags related to open education, we gathered the most extensive dataset of historical open education tweets to date (n = 178,304 tweets and 23,061 users) and conducted a mixed methods analysis of openness from 2009 to 2016. Findings show that the diversity of participants has varied somewhat over time and that the discourse has predominantly revolved around open resources, although there are signs that an increase in interest around pedagogy, teaching, and learning is emerging.